Phase angle as a predictor of nutritional status and quality of life in hemodialysis patients - Elif İradeli; Sema Çalapkorur (PLoS ONE, 2026)
Background and objective Hemodialysis (HD) patients are at high risk for protein-energy wasting and cellular membrane deterioration, which significantly impact their clinical outcomes. Phase angle (PhA) is an objective parameter for assessing nutritional status. As PhA is an indicator of physical function and cellular health, it is hypothesized to correlate with Quality of Life (QoL). This study was carried out to determine the relationship between the PhA and the nutritional status and QoL in patients receiving HD treatment. Methods This cross-sectional study was conducted with 98 patients. Nutritional Risk Score-2002 (NRS-2002) and Malnutrition Inflammation Score (MIS) scales were used to assess the nutritional status of the patients. Physical activity level and QoL were determined by the Physical Activity Questionnaire-Short Form (IPAQ-SF) and Kidney Disease Quality of Life Short Form-36 (KDQOL TM -36), respectively. The body composition of the patients was measured by Inbody S10 and the PhA value was also obtained from this measurement. Results The mean PhA value of the patients was determined as 5.1˚ ± 1.1˚. As a result of the ROC analysis performed using the NRS-2002, the PhA cutoff point was calculated as 4.85˚. It was observed that patients with a PhA less than 4.85˚ had higher MIS and NRS-2002 scores than patients with a PhA greater than this value. KDQOL TM -36 physical and mental component sub-dimension scores of patients with PhA greater than 4.85˚ were found to be higher than those of patients with a PhA less than 4.85˚. It has also been determined that patients with a PhA less than 4.85˚ have a more sedentary lifestyle than patients with a PhA greater than this value. Conclusions PhA is a useful parameter in determining nutritional status and QoL in HD patients. Therefore, PhA may serve as a supportive parameter for evaluating the nutritional and functional status of HD patients in clinical settings.